The role of using social media in family upbringing and social values among students of the University of Nizwa in the Sultanate of Oman - Al Mushaiqri, Mahfouda Rashid Said; Al-Mazidi, Nasser Sulaiyam Nasser; Al-Qassabi, Khalifa Ahmed; Al-Kindi, Jihan Ahmed Nasser; Al-Mahrouqi, Shatha Salim Mohammed (Journal of Humanities & Social Sciences, 2024)
The current study aimed to identify the role of social media on family upbringing and social values among students at the University of Nizwa in the Sultanate of Oman. The study sample consisted of (333) male and female students from Nizwa University in all its four colleges and from different academic years. The study used the descriptive analytical approach, to achieve the study objectives and answer its questions, a tool consisting of five domains was constructed (motives for using social media, family upbringing, social values, positive effects, and negative effects). The validity and reliability of the scale were calculated using appropriate statistical methods, and its value was (0.885). The results of the study showed that Nizwa University students use social media to a large extent, and that the students’ motives for using social media were to communicate with friends regarding their studies and to complete the tasks required of them, and build a network of relationships with others, the results also showed that the positive aspects of social media among Nizwa University students were at a high level, they believe that social media has enabled them to engage in various activities in their lives, they also consider it a field of entertainment and amusement, and it facilitates their buying and selling at any time and place. The results of the study confirmed that the negatives of social media ranged between high, medium and low levels, the results also showed that social media has a role in family upbringing and social values among Nizwa University students, also, there are no statistically significant differences in the use of social media and its role in family upbringing and social values attributed to the gender variable.
Keywords: Social media; family upbringing; social values